Emergency treatment of mastitis in five zaanen goats medicated with a parenteral formulation of tetracycline. Technical note - Bravo Jiménez, Sergio; Fuentes Hernández, Víctor; Orozco Hernández, Rogelio (Revista Científica de la Facultad de Ciencias Veterinarias)
In this report it was described the emergency treatment of an acute case of mastitis in five Zaanen goats, in which initial treatment was carried out using an intramamary commercial presentation, the commercial medication was not available to continue medication: As an alternative it was decided to medicate the affected goats with a parenteral preparation of Oxytetracycline, Emergency treatment was carried out both via, by intramuscular and intramammary routes; the outcome of this treatment was adequate, mastitis was controlled and the microbiological finding showed that Staphyloccocus aureus was the causal agent. All five goats were dried off and subjected to a zynchro program for further kidding, after kidding both udders were milked and production was similar to previous milkings.